The Roles of TNF Signaling Pathways in Metabolism of Bone Tumors - Haiying Zhou; Yanzhao Dong; Ahmad Alhaskawi; Jingtian Lai; Zewei Wang; Sohaib Hasan Abdullah Ezzi; Vishnu Goutham Kota; Mohamed Hasan Abdulla Hasan Abdulla; Zhenyu Sun; Hui Lu; Hui Lu (Frontiers Media S.A., 2022)
The metabolism of bone tumors is extraordinarily complex and involves many signaling pathways and processes, including the tumor necrosis factor (TNF) signaling pathway, which consists of TNF factors and the TNF receptors that belong to the TNF receptor superfamily (TNFRSF). It is appreciated that signaling events and pathways involving TNFRSF components are essential in coordinating the functions of multiple cell types that act as a host defense network against pathogens and malignant cells, the implications of TNFRSF-related signaling pathways on bone tumor metabolism remain to be summarized, which is one of the significant obstacles to the application of TNF-related treatment modalities in the domain of bone oncology. This review will discuss and summarize the anti-tumor properties of important TNFRSF components concerning osteosarcoma, chondrosarcoma, and Ewing sarcoma.